Ontology of Information about an Enterprise Found in Press Articles - Andreasik, Jan (Regional Barometer. Analyses & Prognoses, 2014)
In the paper the ontology of information about an enterprise (OIE ) is presented. The ontology helps to analyse the information about the examined enterprise. The aim of analysis is to isolate information about an enterprise found in business and financial press articles (news items ) in order to define the strategic position of the company. This information is “relative propriety” in the terminology of the Polish philosopher Roman Ingarden’s formal ontology. The author proposes the OIE ontology of information about an enterprise (company ) based on the theory of individual objects by Roman Ingarden. Analysis of information from press news will provide a method for automatic gathering of data on the current state of an enterprise.